Ultrasound and nerve stimulator guided continuous femoral nerve block analgesia after total knee arthroplasty: a multicenter randomized controlled study - Wang,Fen (2015)
BACKGROUND AND OBJECTIVES: Postoperative analgesia is crucial for early functional excise after total knee arthroplasty. To investigate the clinical efficacy of ultrasound and nerve stimulator guided continuous femoral nerve block analgesia after total knee arthroplasty. METHODS: 46 patients with ASA grade I-III who underwent total knee arthroplasty received postoperative analgesia from October 2012 to January 2013. In 22 patients, ultrasound and nerve stimulator guided continuous femoral nerve block were performed for analgesia (CFNB group); in 24 patients, epidural analgesia was done (PCEA group). The analgesic effects, side effects, articular recovery and complications were compared between two groups. RESULTS: At 6 h and 12 h after surgery, the knee pain score (VAS score) during functional tests after active exercise and after passive excise in CFNB were significantly reduced when compared with PCEA group. The amount of parecoxib used in CFNB patients was significantly reduced when compared with PCEA group. At 48 h after surgery, the muscle strength grade in CFNB group was significantly higher, and the time to ambulatory activity was shorter than those in PCEA group. The incidence of nausea and vomiting in CFNB patients was significantly reduced when compared with PCEA group. CONCLUSION: Ultrasound and nerve stimulator guided continuous femoral nerve block provide better analgesia at 6 h and 12 h, demonstrated by RVAS and PVAS. The amount of parecoxib also reduces, the incidence of nausea and vomiting decreased, the influence on muscle strength is compromised and patients can perform ambulatory activity under this condition.